Analiza wybranych neonatalnych czynników ryzyka rozwoju retinopatii wcześniaków - Niwald, Anna; Piotrowski, Andrzej; Grałek, Mirosława (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The aim of the study was to evaluate some of the possible risk factors for retinopathy of prematurity (ROP) treated with laser photocoagulation or cryocoagulation. Material and methods: The study comprised 71 preterm infants with ROP needing treatment and 118 prematures without ROP or with ROP requiring no treatment, as a control group. All infants were born with gestational age ≤ 32 weeks and birth weight ≤ 1500g. The perinatal variables, including some of clinical data, the length of mechanical ventilation as well as continous positive airway pressure (CPAP), duration of total parenteral nutrition and some of laboratory data were analyzed, to evaluate their correlation with the development of ROP. Results: Gestational age before 28 weeks (OR = 5.11), episodes of convulsiones (OR = 2.15), mechanical ventilation for more than 20 days (OR = 5.86) and > 30 days (OR = 7.47), CPAP for more than 5 days (OR = 4.15) and >10 days (OR = 2.84), total parenteral nutrition for more than 10 days (OR = 7.84) and >20 days (OR = 9.02) and elevated peak of alanine aminotransferase (AlAT) levels (OR = 3.17) were significant risk factors for ROP requiring treatment. Conclusions: The opthalmic examination for retinopathy of prematurity requiring laser photocoagulation or cryocoagulation should be obligatory for prematures born ≤ 32 weeks of gestational age, with birth weight ≤ 1500 g.The frequency of the consecutive ophthalmic examinations depends on the severity of prematurity and on the presence and intensification of the risk factors for ROP.